Beyond antibiotics: probiotics as a promising ally against Helicobacter pylori - Yuan, Lin; Yang, Chong; Han, Ying; Yang, Fan; Tu, Huabing (Frontiers in Pharmacology, 2025)
Helicobacter pylori (H. pylori) is considered a key causative agent of gastritis, peptic ulcer, and gastric cancer, affecting more than half of the world’s population. The eradication rate of antibiotic therapy gradually decreases due to the increased risk of resistance. Recent studies have shown that probiotics have good potential in the treatment of H. pylori infection. Several studies involving both human and animal models have demonstrated that probiotic interventions can inhibit H. pylori growth, attenuate H. pylori-induced gastritis, and enhance the eradication rate of antibiotics while reducing side effects. However, there remains some debate regarding the effective benefits of probiotics. The recently published reviews have not systematically elaborated on the differences in outcomes resulting from the use of probiotics of various types and doses, or the combination of probiotics with medications. They have primarily focused on animal studies, without addressing the heterogeneity of results observed in clinical research and the underlying mechanisms, thus failing to provide more high-quality evidence. This review aims to discuss the mechanisms of H. pylori infection in humans, the effects of probiotics in treating H. pylori infection, and the pathways and molecular mechanisms by which probiotics inhibit H. pylori. Future challenges include identifying effective strains, determining optimal doses and treatment durations, standardizing experimental protocols, considering individual variability, and further elucidating the specific molecular mechanisms and long-term impacts of probiotic therapy in H. pylori infection.